Diseño de una máquina automática cortadora de textiles compuestos por fibras sintéticas (2017)
The development of the degree work, was initially developed with an assessment of the current situation of the company, operating parameters were made, presented and studied the design alternatives and the calculations and design of the machine, the drag system, the cutting system and the behavior of the structure with respect to the loads that it had to support and resist, were carried out, following this the proceeding was carried out. analysis by finite elements of the points and the most critical parts of the machine and the structure, the planes of the systems and subsystems that make up the machine were made, the operation, assembly, maintenance and safety and health manuals were made occupational; Subsequently, the project's financial evaluation, conclusions and recommendations were carried out.